Developing Secondary Schools' Novice Teachers Induction Model (SSNTInM): Facilitating and Enhancing Professional Teacher Development to Meet NKRA On Quality Education - Awang, Mohd Isha; Shaari, Abdull Sukor (UUM, 2021)
Generally, the purpose of this study is to examine the level of needs and satisfaction levels of new teachers from several aspects. In particular, this study aims to explain (a) the level of needs of new teachers in terms of mentoring, school support, key information, implementation of PdPc and co-curricular activities, (b) level of teacher satisfaction in terms of mentoring, school support, key information, implementation PdPc and co-curricular activities; and (c) the influence of needs factors on satisfaction among new teachers. This survey study involved a total of 177 new teachers who were taken at random. The instrument used in this study is a questionnaire modified from the instrument Induction Activities Teacher Questionaire: Study of Teacher Induction Programs. The findings show that the level of teacher needs in terms of mentoring, school support, key information, implementation of PdPc and co-curricular activities are very important to new teachers. However, in terms of the level of satisfaction with these factors is at a moderate level only. Only the level of satisfaction related to the key information needed is achieved at a high level. This study has important implications for the needs of the school, JPN and KPM to provide continuous support to new teachers to enable them to develop their level of professionalism.